The broken hearts gallery [videorecording (DVD)] - Krinsky, Natalie, 1982-; Viswanathan, Geraldine, 1995-; Montgomery, Dacre, 1994-; Ambudkar, Utkarsh; Peters, Bernadette (Sony Pictures Home Entertainment, 2020)
Dumped by her boyfriend, a New York art gallery assistant creates an exhibit for souvenirs from past relationships.